2021
DOI: 10.3390/molecules26175152
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combination Treatments with Astaxanthin-Loaded Microparticles and Pentoxifylline on Intracellular ROS and Radiosensitivity of J774A.1 Macrophages

Abstract: Radiation-induced fibrosis (RIF) is a serious, yet incurable, complication of external beam radiation therapy for the treatment of cancer. Macrophages are key cellular actors in RIF because of their ability to produce reactive oxidants, such as reactive oxygen species (ROS) and inflammatory cytokines that, in turn, are the drivers of pro-fibrotic pathways. In a previous work, we showed that phagocytosis could be exploited to deliver the potent natural antioxidant astaxanthin specifically to macrophages. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…RIF is a serious long-term side effect that compromises respiratory, hepatic, intestinal, and urinary functions in cancer patients exposed to radiotherapy [ 69 ]. Its pathogenesis is still not fully understood, although it is known that macrophages have a central role in RIF for their ability to produce reactive oxygen species (ROS), and inflammatory molecules that in turn trigger the fibrotic pathways in injured tissues [ 70 ]. They showed [ 67 ] in vitro experiments that these microparticles were not cytotoxic for macrophage cells and could be taken up only by them.…”
Section: Innovative Approaches To Target Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…RIF is a serious long-term side effect that compromises respiratory, hepatic, intestinal, and urinary functions in cancer patients exposed to radiotherapy [ 69 ]. Its pathogenesis is still not fully understood, although it is known that macrophages have a central role in RIF for their ability to produce reactive oxygen species (ROS), and inflammatory molecules that in turn trigger the fibrotic pathways in injured tissues [ 70 ]. They showed [ 67 ] in vitro experiments that these microparticles were not cytotoxic for macrophage cells and could be taken up only by them.…”
Section: Innovative Approaches To Target Macrophagesmentioning
confidence: 99%
“…Astaxanthin-loaded (ASX) microparticles inhibited the production of bioavailable TGF-β by interfering with the activity of intracellular convertases, a class of enzymes implicated in the post-translational processing and activation of numerous pro-proteins (e.g., TGF-β). Further, they demonstrated that the effects of astaxanthin-loaded microparticles could be further potentiated by combination treatment with pentoxifylline [ 70 ], a drug approved for the treatment of claudication as it has anti-inflammatory properties (e.g., inhibition of TNF-α production and signaling) and improves rheological properties of blood and wound healing [ 71 ]. Given in combination with ASX microparticles, that on their own inhibit active TGF-β release by targeted macrophages, might result in more effective treatments against inflammation and fibrosis.…”
Section: Innovative Approaches To Target Macrophagesmentioning
confidence: 99%
“…To evaluate synergistic effects of dual drug treatments on LTF and RSK activation, we used a two-way ANOVA to assess the interaction between two treatment factors [26][27][28][29] . The significance of the combined-drug interaction was used to evaluate the null hypothesis that the combined effect of two drugs is merely additive (Fig.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…3A, oval). To analyze whether NSC and rolipram acted synergistically, we performed a two-way ANOVA as suggested by Slinker (1998) and applied by multiple groups [27][28][29] . Two drugs are deemed to act synergistically if the F statistic for the interaction effect is less than the critical value of 0.05.…”
Section: Analysis Of Synergism For the Effect Of The Drug Combination...mentioning
confidence: 99%
“… Synthetic compounds, i.e., alkyl thiols [ 10 ], dimethyl sulfoxide [ 11 ], metformin and S63845 [ 12 ], the ruthenium complex [Ru(Phen) 3 ] 2+ [ 13 ], and copper-based compounds—Casiopeinas [ 14 ]. Different formulations, i.e., peptide fractions from germinated soybeans conjugated to Fe 3 O 4 nanoparticles [ 15 ] and astaxanthin microparticles in combination with pentoxifylline [ 16 ]. Proteins (aquaporins [ 17 ]) and nuclear factor erythroid-2-related factor 2 (NRF2) [ 8 ].…”
mentioning
confidence: 99%